Poorly Differentiated Uterine or Cervical Sarcoma in a Young Dog - Michelle C. Cora; Jennifer A. Neel (Case Reports in Veterinary Medicine)
A 1.5 year old, female, spayed, Labrador retriever with a history of three abdominal surgeries within the previous two months presented to the North Carolina State University Veterinary Teaching Hospital for evaluation of a pelvic inlet mass causing fecal tenesmus, obstipation, and dysuria. Abdominal ultrasound revealed a caudal abdominal mass extending into the pelvic cavity. Cytologic evaluation of the mass showed a pleomorphic round to fusiform cell population with histiocytic and suppurative inflammation. The primary differential was neoplasia, but inflammation with cellular pleomorphism could not be excluded. Via histopathology and immunohistochemistry, a diagnosis of poorly differentiated sarcoma originating from the uterus or cervix with widespread intra-abdominal dissemination and metastasis was made. Sarcomas of any type are rare in young dogs with only sporadic cases of poorly or undifferentiated sarcomas reported. This case is a unique presentation of an aggressive, poorly differentiated sarcoma arising from the cervix or uterus in a young dog and illustrates the importance of histologic evaluation of surgically resected tissues that are abnormal in appearance.